ISCA1 mutation in a patient with infantile-onset leukodystrophy causes defects in mitochondrial [4Fe–4S] proteins. (14th May 2018) - Torraco, Alessandra; Stehling, Oliver; Stümpfig, Claudia; Rösser, Ralf; De Rasmo, Domenico; Fiermonte, Giuseppe; Verrigni, Daniela; Rizza, Teresa; Vozza, Angelo; Di Nottia, Michela; Diodato, Daria; Martinelli, Diego; et al.
Abstract: Multiple mitochondrial dysfunction syndromes (MMDS) comprise a group of severe autosomal recessive diseases characterized by impaired respiration and lipoic acid metabolism, resulting in infantile-onset mitochondrial encephalopathy, non-ketotic hyperglycinemia, myopathy, lactic acidosis and early death. Four different MMDS have been analyzed in detail according to the genes involved in the disease, MMDS1 ( NFU1 ), MMDS2 ( BOLA3 ), MMDS3 ( IBA57 ) and MMDS4 ( ISCA2 ). MMDS5 has recently been described in a clinical case report of patients carrying a mutation in ISCA1, but with no further functional analysis. ISCA1 encodes a mitochondrial protein essential for the assembly of [4Fe– 4S] clusters in key metabolic and respiratory enzymes. Here, we describe a patient with a severe early onset leukodystrophy, multiple defects of respiratory complexes and a severe impairment of lipoic acid synthesis. A homozygous missense mutation in ISCA1 (c.29T>G; p.V10G) identified by targeted MitoExome sequencing resulted in dramatic reduction of ISCA1 protein level. The mutation located in the uncleaved presequence severely affected both mitochondrial import and stability of ISCA1. Down-regulation of ISCA1 in HeLa cells by RNAi impaired the biogenesis of mitochondrial [4Fe– 4S] proteins, yet could be complemented by expression of wild-type ISCA1 . In contrast, the ISCA1 p.V10G mutant protein only partially complemented the defects, closely resembling the biochemical phenotypes observed for ISCA1 patient fibroblasts. Collectively, our comprehensive clinical and biochemical investigations show that the ISCA1 p.V10G mutation functionally impaired mitochondrial [4Fe– 4S] protein assembly and hence was causative for the observed clinical defects.